TECHNICAL VISIT AS A RESOURCE FOR LEARNING PRODUCTION MANAGEMENT: AN EXPERIENCE REPORT (CIPEEX, 2024)
THE TECHNICAL VISITS CONFIGURE A WAY TO ADD MORE PRACTICAL KNOWLEDGE IN SEVERAL AREAS, PROVIDING EXPERIENCES BEYOND THE THEORETICAL ACTIVITIES. IN THIS CONTEXT, ON OCTOBER 1, 2022, THE STUDENTS OF THE ADMINISTRATION COURSE OF THE EVANGELICAL UNIVERSITY OF GOIS - CAMPUS CERES KNEW THE ACTIVITIES DEVELOPED AS WELL AS THE PROCESS OF PRODUCTION OF DRY, WET FOOD AND SNACKS FOR ANIMALS OF AN INDUSTRY. THE PROPOSED OBJECTIVE IS TO REPORT THE LIVED EXPERIENCE CONFRONTING WITH THE THEORETICAL CONTENT PREVIOUSLY TAUGHT IN THE CLASSES. WHEN ENTERING THE FACTORY FACILITIES, THE HISTORY, MISSION, VISION AND VALUES, THE PRODUCT PORTFOLIO, THE STAGES OF THE PROCESS, AS WELL AS THE OBJECTIVES AND GOALS OF THE ORGANIZATION WERE PRESENTED. THEN, THERE WAS THE TRAINING OF ACADEMICS WITH THE PERSONAL PROTECTION EQUIPMENT REQUIRED BY THE REGULATORY STANDARD Nº 06 (NR 06) TO ENTER THE VARIOUS AREAS OF INDUSTRY. FROM THIS, IT WAS KNOWN THE PROCESS, FROM THE RECEIPT OF RAW MATERIAL THAT IS NECESSARY FOR THE DEVELOPMENT OF ACTIVITIES, THROUGH THE FOLLOWING MACHINERY: EXTRUDER, DRYER AND COOLER, FOLLOWING FOR THE FILLING AND STORAGE OF THE PRODUCT.&NBSP; THROUGHOUT THE PRESENTATION OF THE STAGES OF THE PRODUCTION PROCESS, THE RELEVANCE OF THE IMPLEMENTATION OF THE TOTAL QUALITY PHILOSOPHY AS A FUNDAMENTAL MEANS TO ACHIEVE EXCELLENCE IN PRODUCT PRODUCTION WAS EMPHASIZED. THE INDUSTRY USES JUST IN TIME AS A PRODUCTION MANAGEMENT SYSTEM, IN ORDER TO MANAGE BOTH PURCHASES, PRODUCTION AND SALES, IN ORDER TO AVOID WASTE DURING PERIODS OF SEASONALITY THROUGHOUT THE YEAR. IN ADDITION, THE COMPANY RECOGNIZES AND ADOPTS THE ESG (ENVIRONMENTAL, SOCIAL AND GOVERNANCE) APPROACH, AS A TOOL THAT WORKS TOWARDS SOCIAL GOALS AND IS NOT LIMITED TO THE PURSUIT OF PROFIT MAXIMIZATION. IN THIS WAY, FROM THE EXPERIENCED REPORT, IT IS DEMONSTRATED THE IMPORTANCE OF TOTAL QUALITY IN ORDER TO CONSIDER ENVIRONMENTAL ISSUES, AVOIDING THE DETERIORATION OF NATURAL RESOURCES. THEREFORE, IT CAN BE INFERRED THAT THE QUALITY CONTROL OF THE PET INDUSTRY IS AS STRICT AS THAT OF THE FOOD INDUSTRY FOR HUMANS.
Keywords: ESG; Production; Quality; Visit